Lower Extremity Arterial Duplex, Toe-Brachial Index, and Computed Tomography Angiography Examinations in Peripheral Arterial Disease: A Case Presentation. (November 2017) - Viduetsky, Alexander; Benedict, Matthew
Peripheral arterial disease (PAD) commonly results from progressive narrowing of arteries in the extremities because of atherosclerosis. More than 8 million people in the United States have PAD. The majority of individuals with PAD are seniors with one or more cardiovascular disease risk factors. Because patients with PAD may be asymptomatic, the true incidence of PAD may be underreported. Accurate and timely diagnosis of PAD is very important for optimal treatment.